Harvard business review on corporate governance (Harvard Business School P. BostonUS, 2000)
Focuses on policy and strategic challenges for senior managers who work with boards or deal with governance issues. Identifies the 2 critical responsibilities of boards as: oversight of long-term company strategy; and the selection, evaluation, and compensation of top management. Deals with topics including: empowering the board; the board's role in CEO succession; appraising boardroom performance; and redrawing the line between the board and the CEO.
Located in the Learning Resource Centre